Attractants from tilapia skin, Oreochromis niloticus (Perciformes: Cichlidae), to reduce feed waste in aquaculture farms (UNED Research Journal, 2020)
Introduction: Aquaculture has emerged as an alternative to traditional fishing due to the collapse of fish populations from intensive off-shore fishing. However, many aquaculture farms could reduce feed waste by using chemical attractants to concentrate fish during feeding. Objective: To test a tilapia skin attractant. Methods: Attractants were tested with 16159 mature and immature tilapias in confined indoor freshwater and saltwater ponds, and in outdoor ponds. Results: With the attractant, the immature fish approached food faster than in the controls (p
Keywords: Chemical cues; Solvent; Aquaculture; Fishing; Methanol